Unintended consequences of the increased asset threshold for FDICIA internal controls: Evidence from U.S. private banks - Jin, Justin Yiqiang; Kanagaretnam, Kiridaran; Lobo, Gerald J. (Journal of Banking & Finance, 2013)
We examine the unintended consequences of the 2005 increase from 500 million to 1 billion in the asset threshold for the Federal Deposit Insurance Corporation Improvement Act (FDICIA) internal control reporting requirements. We focus on a test sample of banks that increased their total assets from between 100 million and 500 million prior to the change in regulation to between 500 million and 1 billion within two years following the change. These “affected” banks are no longer subject to the internal control requirements but would have been had the regulation not been changed. We hypothesize that these affected banks are likely to make riskier loans, which will increase the likelihood of failure during the crisis period. We find evidence consistent with this hypothesis. Affected banks have higher likelihood of failure during the crisis period than banks from two different control samples. We also find that auditor reputation (i.e., whether the bank is audited by a Big 4 auditor or an industry specialist auditor) has a moderating effect on the likelihood of failure for these affected banks.